THE APPLICATION OF DIGITAL MARKETING COMMUNICATION IN FACING THE PHENOMENON OF TIKTOK SHOPPERTAINMENT AS A MARKETING COMMUNICATION STRATEGY FOR UMKM - Pakpahan J.P.; Avina D.A.A. (Russian Journal of Agricultural and Socio-Economic Sciences)
This research explores how Micro, Small, and Medium Enterprises (MSMEs) apply digital marketing communication to deal with the TikTok Shoppertainment phenomenon using the 4C marketing communication model (Clarity, Consistency, Credibility, and Competitiveness). This phenomenon shows a change in consumer behavior that switches to entertainment content and online shopping on TikTok, as well as an algorithm game carried out by TikTok. This research aims to understand the marketing communication strategies used by MSMEs, as well as identify challenges and solutions in the implementation of digital marketing, especially on TikTok. The research method used is a qualitative approach through in-depth interviews with three successful MSME owners in the fashion sector who use TikTok as a marketing communication strategy and use documentation as a complement. The results show that TikTok provides a great opportunity for MSMEs to promote products and increase engagement. MSMEs such as Sani Signature, By.Lumicasa, and Arabasic have successfully adapted to competitive digital market dynamics and dynamic consumer preferences. In addition, the three MSME players understand the importance of audience engagement and focus on increasing credibility by understanding relevant, informative, and entertaining content. However, MSMEs are also facing challenges such as competition from artists and influencers, the complexity of TikTok's algorithm, and limited human resources and expertise. To overcome these challenges, MSMEs can increase collaboration between MSMEs, conduct education on effective content strategies, and strengthen internal competencies.